Analisis Pengaruh Rasio Lancar, Perputaran Piutang, dan Rasio Hutang terhadap Return on Asset pada Perusahaan Food and Beverage - Rahmawati, Nor; Wiyono, Gendro; Sari, Pristin Prima (Universitas Batanghari, 2024)
This study aims to analyze the effect of current ratios, accounts receivable turnover, and debt to asset ratios on ROA in Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2018 to 2021. The population taken in this study was 72 companies. With a sample of 25 companies. The sampling technique is using purposive sampling technique. The place of research used is the Indonesia Stock Exchange on financial report data for food and beverage companies. The time for data collection is from 2018 to 2021. The results of the current ratio variable test have a significance value of 0.296 > 0.05 with a t value of 1.053 and a coefficient of 0.114. Receivables turnover variable has a significance value of 0.421 > 0.05 with a t value of 0.810 and a coefficient value of 0.073. The debt to asset ratio variable has a significance value of 0.000 < 0.05 with a t value of -5.814 and a coefficient value of -0.661. Based on the research results, the following results are obtained: a. The current ratio variable has no effect on return on assets. b. Receivables turnover variable has no effect on return on assets. c. The debt ratio variable has an effect on return on assets..